2011
DOI: 10.1186/1471-2164-12-501
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptome changes induced by MDV in marek's disease-resistant and -susceptible inbred chickens

Abstract: BackgroundMarek's disease (MD) is a lymphoproliferative disease in chickens caused by Marek's disease virus (MDV) and characterized by T cell lymphoma and infiltration of lymphoid cells into various organs such as liver, spleen, peripheral nerves and muscle. Resistance to MD and disease risk have long been thought to be influenced both by genetic and environmental factors, the combination of which contributes to the observed outcome in an individual. We hypothesize that after MDV infection, genes related to MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 56 publications
3
41
0
1
Order By: Relevance
“…The same SNP-fingerprint showed three RCS (RCS-B, RCS-M, and RCS-S) were more different from line 7 2 than line 6 3 as expected (Figure 3). Our recent study on gene expression profiling indicated that global gene expressions were significantly different between the chickens of lines 6 3 and 7 2 as well [36]. In addition to genetic differences, epigenetic differences now have been found to commonly exist between the two lines of chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same SNP-fingerprint showed three RCS (RCS-B, RCS-M, and RCS-S) were more different from line 7 2 than line 6 3 as expected (Figure 3). Our recent study on gene expression profiling indicated that global gene expressions were significantly different between the chickens of lines 6 3 and 7 2 as well [36]. In addition to genetic differences, epigenetic differences now have been found to commonly exist between the two lines of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed the primary lymphoid organ size and IgG level differ between the lines 6 3 and 7 2 [34,35]. Data from our recent collaborative studies showed that profiles of global gene expression with or without MDV challenge differ between the highly inbred line 6 3 and 7 2 and one recombinant congenic strain [36]. Using miRNA microarray, it was demonstrated that miRNAs were differentially expressed between line 6 3 and 7 2 chickens post MDV challenge [37].…”
Section: Introductionmentioning
confidence: 86%
“…Our previous studies revealed that DNMTs were differentially expressed in the line 6 3 and line 7 2 chickens, 14 especially at 21 DPI, when the virus was reactivated from the latent stage. 6,15,16 The results point to a profound distinction between epigenetic profiles and expression of selected genes in line 6 3 and 7 2 chickens. The interesting finding that many of these differences, particularly in response to MDV challenge, affect genes of the immune system or tumor progression and related pathways provides a strong rationale for pursuit of our hypothesis that epigenetic signatures are associated with resistance or susceptibility of MDV induced tumorigenesis.…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, these comparative analyses revealed differentially enriched regions between susceptible and resistant chicken lines [85,86], suggesting the existence of an "epigenetic signature" for disease susceptibility. Moreover, Song and collaborators demonstrated that the HPTM profile was modulated after infection at the loci of genes involved in the immune system response [84], corresponding to expression changes after infection [88]. For example, at the locus of CD8α in spleen (for which expression was slightly or highly increased after infection in susceptible and resistant chicken lines, respectively), H3K4me3 was increased concomitantly to gene expression depending on the line [84].…”
Section: The Chicken Hptm Landscapementioning
confidence: 99%